Efficiency of salicylic acid or methyl jasmonate immersions on internal browning alleviation and physicochemical quality of Queen pineapple cv. "Sawi" fruit during cold storage. Issue 12 (9th October 2019) - Sangprayoon, Preyanuch; Supapvanich, Suriyan; Youryon, Pannipa; Wongs‐Aree, Chalermchai; Boonyaritthongchai, Panida
Abstract: The pineapples were dipped in salicylic acid (SA) (2.5 or 5.0 mM) or methyl jasmonate (MeJA) (0.01 or 0.1 mM) for 1, 2, or 3 hr and then held at 13 ± 1°C for 10 days. The parameters were determined after left the fruits at 25°C for 2 days. It was found that, in the tissue adjacent to the core, 5.0 mM SA for 2 hr and 0.01 mM MeJA for 3 hr alleviated chilling injury (CI) and maintained color than other treatments. The MeJA immersions lowered CI score, electrolyte leakage, and malondialdehyde content greater than other treatments. SA and MeJA immersions retarded polyphenol oxidase activity, total phenols, and induced antioxidant activity during storage. In the pulp tissue, SA treatment increased ascorbic acid and total sugar contents, and MeJA immersions enhanced bioactive compound and antioxidant enzyme activities than SA immersion. Therefore, MeJA immersions could alleviate CI and enhance antioxidant better than other treatments of pineapples during cold storage. Practical applications: Postharvest immersion at the optimum concentration of SA or MeJA can be applied for commercial scale in order to alleviate chilling of "Sawi" pineapple fruit during storage. MeJA treatment enhances antioxidant activity and reduces internal browning better than SA treatment in pineapple.